Physical origin of the non-physical spin evolution of MAXI J1820 + 070. Issue 2 (6th April 2021) - Guan, J; Tao, L; Qu, J L; Zhang, S N; Zhang, W; Zhang, S; Ma, R C; Ge, M Y; Song, L M; Lu, F J; Li, T P; Xu, Y P; et al.
ABSTRACT: We report on the Insight -HXMT observations of the new black hole X-ray binary MAXI J1820+070 during its 2018 outburst. Detailed spectral analysis via the continuum fitting method shows an evolution of the inferred spin during its high soft sate. Moreover, the hardness ratio, the non-thermal luminosity and the reflection fraction also undergo an evolution, exactly coincident to the period when the inferred spin transition takes place. The unphysical evolution of the spin is attributed to the evolution of the inner disc, which is caused by the collapse of a hot corona due to condensation mechanism or may be related to the deceleration of a jet-like corona. The studies of the inner disc radius and the relation between the disc luminosity and the inner disc radius suggest that, only at a particular epoch, did the inner edge of the disc reach the innermost stable circular orbit and the spin measurement is reliable. We then constrain the spin of MAXI J1820 + 070 to be $a_*=0.2^{+0.2}_{-0.3}$ . Such a slowly spinning black hole possessing a strong jet suggests that its jet activity is driven mainly by the accretion disc rather than by the black hole spin.